2005
DOI: 10.1002/jssc.200500050
|View full text |Cite
|
Sign up to set email alerts
|

Use of automated direct sample introduction with analyte protectants in the GC–MS analysis of pesticide residues

Abstract: Automated large-volume direct sample introduction, or difficult matrix introduction (DMI), was investigated in the determination of 44 pesticide residues possessing a wide range of physico-chemical properties (volatility, polarity, pK(a)) in fruit-based baby food by means of gas chromatography-mass spectrometry (GC-MS) with a quadrupole mass analyzer. DMI has advantages over traditional injection because large volumes (up to 30 microL) of potentially dirty sample extracts can be injected into the GC-MS, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Since then, Atas/GL Science developed an automated DSI device compatible with their Optic PTV, and marketed it as difficult matrix injection (DMI) [26,27]. Recently, the company has revised their automated approach with a second generation product.…”
Section: Sample Injection and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Since then, Atas/GL Science developed an automated DSI device compatible with their Optic PTV, and marketed it as difficult matrix injection (DMI) [26,27]. Recently, the company has revised their automated approach with a second generation product.…”
Section: Sample Injection and Analysismentioning
confidence: 98%
“…Analyte protectants were 3-ethoxy-1,2-propanediol, D-sorbitol, L-gulonic acid c-lactone with 95% or better purity obtained from Sigma and Fluka. A composite stock solution of analytical protectants (10 : 1 : 1 mg/mL of 3-ethoxy-1,2-propanediol, D-sorbitol, L-gulonic acid c-lactone) was prepared in 7 : 3 water/MeCN as described by Cajka et al [27]. A quality check standard solution of 16 lg/mL triphenylphosphate (TPP) was prepared in MeCN containing 1.6% FA.…”
Section: Reagents and Solutionsmentioning
confidence: 99%
“…The matrix shields active sites in the liner and column, which reduces interaction of the analytes on these sites, and leads to enhanced analyte peaks. This effect is most pronounced for polar analytes (typically those with strong hydrogen bonding potential) [25]. Looking at those compounds for which this enhancement is not expected (e.g.…”
Section: Matrix Effectmentioning
confidence: 99%
“…[1][2][3][4][5] In our previous study, 6) the matrix components of different types of agricultural products, which were pretreated using the Multiresidue Method for Agricultural Chemicals by GC-MS (Agricultural Products) in the "Analytical Method for Residual Compositional Substances of Agricultural Chemicals, Feed Additives, and Veterinary Drugs in Food" under the Japanese Positive List System (JPL) of Ministry of Health, Labour and Welfare (hereafter, called the JPL method), were examined and some common matrices, monoacylglycerols, tocopherols, and sterols, were found in the sample solution. We also concluded that the monoacylglycerols were the most significant component among them.…”
Section: Introductionmentioning
confidence: 99%